2020
DOI: 10.1002/ece3.6766
|View full text |Cite
|
Sign up to set email alerts
|

Foraging in a dynamic environment: Response of four sympatric sub‐Antarctic albatross species to interannual environmental variability

Abstract: Seasonal and annual climate variations are linked to fluctuations in the abundance and distribution of resources, posing a significant challenge to animals that need to adjust their foraging behavior accordingly. Particularly during adverse conditions, and while energetically constrained when breeding, animals ideally need to be flexible in their foraging behavior. Such behavioral plasticity may separate “winners” from “losers” in light of rapid environmental changes due to climate change. Here, the foraging b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 114 publications
1
7
0
Order By: Relevance
“…However, in our study, no clear and consistent habitat preferences could be detected (Figure S9). While our aim in this study was not to investigate habitat preferences in detail, but rather to control habitat models by environmental variability to directly investigate intraspecific competition, our results confirmed that wandering albatrosses displayed high flexibility in habitat preferences (Carpenter‐Kling et al., 2020), from both sexes and sites. While more advanced analyses on the differences in flight tactics between sexes in relation to more detailed wind measurements (e.g.…”
Section: Discussionsupporting
confidence: 62%
“…However, in our study, no clear and consistent habitat preferences could be detected (Figure S9). While our aim in this study was not to investigate habitat preferences in detail, but rather to control habitat models by environmental variability to directly investigate intraspecific competition, our results confirmed that wandering albatrosses displayed high flexibility in habitat preferences (Carpenter‐Kling et al., 2020), from both sexes and sites. While more advanced analyses on the differences in flight tactics between sexes in relation to more detailed wind measurements (e.g.…”
Section: Discussionsupporting
confidence: 62%
“…climate change, distribution, marine mammals, prediction, projection, seabirds, Southern Ocean these marine predators may be somewhat plastic in their response to environmental variability (e.g. Carpenter-Kling et al, 2020), the tight coupling between climate and biophysical features in their foraging areas (e.g. Bost et al, 2015) means that climate change has the potential to significantly influence their future distributions (Grose et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The pre-moult distribution of African penguins departing from Dassen Island and Bird Island showed significant inter-annual variability. Plastic foraging distributions during the pre- and post-moult stages has been demonstrated for several penguin species 19 , 63 , 64 , 68 and other marine predators such as volant seabirds and seals 79 84 . The marine environment is highly dynamic with numerous biophysical factor determining the spatio-temporal distribution of prey 85 .…”
Section: Discussionmentioning
confidence: 99%